The CMHC in Ajax, Ontario: 1948-1950 - McGeachy, Robert (Ontario History)

(untitled) (The Ontario Historical Society, 2006)
Between 1948 and 1950, the federal crown corporation, Central Mortgage and Housing Corporation (CMHC) sold off most of its extensive holdings in the small Ontario community of Ajax. This process was surprisingly arduous and complex as the CMHC attempted to ensure that the community and the immediate surrounding area had suitable plans to regulate potentially uncontrolled growth. The local federal member of Parliament and residents were among the actors who resisted the CMHC efforts. Ontario governmental officials also played a complex almost duplicitous role in the proceedings. Eventually, the CMHC withdrew from Ajax without achieving most of its objectives. This case study highlights the complications that can occur when three levels of government become involved in a contentious undertaking such as establishing a new municipal government.